1998
DOI: 10.1007/s11357-998-0004-x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of α-ketoglutarate-and pyruvate dehydrogenase complexes in E. coli by a glutathione S-transferase containing a pathological length poly-Q domain: A possible role of energy deficit in neurological diseases associated with poly-Q expansions?

Abstract: At least seven adult-onset neurodegenerative diseases, including Huntington's disease (HD),

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…One preliminary study in the putamen of brains from controls and HD patients suggests that KGDHC activity is reduced [ 16 ]. E. coli with 62 CAG repeats exhibit significantly impaired KGDHC activity compared to controls [ 38 , 39 ]. DLST (dihydrolipoyl succinyl transferase) is one of the three subunits of the KGDHC.…”
Section: Discussionmentioning
confidence: 99%
“…One preliminary study in the putamen of brains from controls and HD patients suggests that KGDHC activity is reduced [ 16 ]. E. coli with 62 CAG repeats exhibit significantly impaired KGDHC activity compared to controls [ 38 , 39 ]. DLST (dihydrolipoyl succinyl transferase) is one of the three subunits of the KGDHC.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors have used transfected Escherichia coli to study the effects of Q n ‐expanded proteins on the intracellular aggregates that form in these bacteria. E. coli does not possess transglutaminase activity (Cooper et al, 1998). Indeed, transfection of this bacterium with a transglutaminase from a different bacterium results in inhibition of cell growth and lysis (Takehana et al, 1994).…”
Section: Noncovalent Interactions and Aggregate Formationmentioning
confidence: 99%
“…Scherzinger et al (1997) reported that a glutathione S ‐transferase (GST)‐fusion protein containing an expanded Q n domain forms amyloidlike protein aggregates (indicative of β‐pleated sheet formation) in E. coli . GSTQ n constructs containing small Q n domains (n = 10‐35) are not toxic to E. coli , whereas GSTQ n ‐fusion proteins containing longer repeats are toxic (Onodera et al, 1996 ; Cooper et al, 1998). Aggregate formation, however, occurs much more rapidly in transfected E. coli than in the (CAG) n /Q n ‐expansion diseases where cellular aggregate formation may take many years.…”
Section: Noncovalent Interactions and Aggregate Formationmentioning
confidence: 99%